2011
DOI: 10.1007/s12646-011-0074-1
|View full text |Cite
|
Sign up to set email alerts
|

Illness Beliefs and Coping Strategies of Diabetic Women

Abstract: The present study examines the relationship between illness beliefs and coping strategies in diabetic women patients. Measures of illness beliefs and coping strategies were administered to 100 diabetic women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
(59 reference statements)
1
5
0
Order By: Relevance
“…The approach coping affects HRQoL positively, in the sense that the more the use of the coping approach, the HRQoL will also increase. This is consistent with the findings that approach coping mechanisms are associated with positive outcomes [32]. This is also in line with the finding that state when individuals apply active coping and acceptance (type of approach coping), there is a tendency that individuals have a better quality of life [33][34].…”
Section: Discussionsupporting
confidence: 91%
“…The approach coping affects HRQoL positively, in the sense that the more the use of the coping approach, the HRQoL will also increase. This is consistent with the findings that approach coping mechanisms are associated with positive outcomes [32]. This is also in line with the finding that state when individuals apply active coping and acceptance (type of approach coping), there is a tendency that individuals have a better quality of life [33][34].…”
Section: Discussionsupporting
confidence: 91%
“…Few women reported feeling that there was an existential reason for their illness. Awasthi and Mishra (2011) found that patients who believed that their disease emanated from supernatural sources were inclined to use emotion-focused coping strategies. In our sample, even though some women alluded to an existential reason behind their illness, they still utilised a combination of problem- and emotion-focused coping.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have found that women with coeliac disease also employed planning as a coping strategy (Jacobsson et al, 2012). Awasthi and Mishra (2011) found that diabetic women who believed strongly that the cause of their illness emanated from environmental, supernatural and psychosocial sources utilised emotionfocused coping strategies, whereas those who believed less strongly in these sources were more likely to use problem-focused coping strategies.…”
Section: Copingmentioning
confidence: 99%
“…Several studies have examined a connection between illness related beliefs and health behavior among women suffering from the cervical cancer and/or diabetes (Awasthi & Mishra, 2011Awasthi, Mishra, & Shahi, 2006;Awasthi, Mishra, & Singh, 2018;Mishra, Awasthi, & Singh, 2004). In cancer patients, "doctor control" was found to reduce psychological and interpersonal consequences as well as the pain caused by the illness, and also enhanced their optimistic view of illness recovery.…”
Section: Coping Strategies Illness Beliefs and Health Outcomesmentioning
confidence: 99%